Determinants of electricity production from renewable source excluding hydroelectricity in selected East African countries: Panel ARDL approach - Teshager Mazengia Asratie (Cogent Economics & Finance, 2022)
Though East Africa has ample resource endowments for electricity production, the region has the lowest performance in generating electricity, and millions of people are living without access to electricity. To fill the electricity gap countries used fossil fuels as the major source of energy, but electricity production from a renewable resource is lower. Therefore, this study aimed to identify determinant factors of electricity production from renewable resources excluding hydropower sources. Panel data for five East African countries for the period 1998 to 2019 were used, and it was examined using pooled mean group panel ARDL estimation technique. The estimation result revealed that in the long- and short-run GDP per capita growth, population growth, energy consumption per capita, and energy import have a positive significant effect on electricity production from renewable resources other than hydropower, while political instability, electricity production from hydropower, and electricity production from oil, gas, and coal have a negative significant effect. However, in the short run, energy use and resource rent percentage of GDP have positive and negative significant effects, respectively, but in the long run, the two variables have no significant effect. Error correction coefficient is negative 0.64, which indicates that the deviation from long-run disequilibrium adjusts toward equilibrium at a rate of 64% per year. Based on the results, this study recommends that the government improve the performance of GDP growth by quality education, lower lending interest rate, improving political stability through controlling internal conflicts caused by differences in religion and ethnicity, and improving energy security.
Keywords: 330; electricity production; panel ARDL; renewable; East Africa